Response of Haptera Growth to Different Frequencies of Light in Deep Water Agarum fimbriatum and Shallow Water Alaria marginata - Nigam, Nirupam; Dethier, Megan; Mumford, Tom (Friday Harbor Laboratories, 2014)
Light plays an important role in kelp ecology as an energy source and as an important kelp growth regulator. It induces a negative phototropic response in kelp haptera. Because longer wavelengths of light are available at shallower depths in additions to shorter wavelengths, it was hypothesized that kelp species generally inhabiting shallower water (e.g., Alaria marginata) would have a phototropic response to red (720-740 nm), green (520-540 nm), and blue (420-440 nm) light. Species generally inhabiting deeper water (e.g., Agarum fimbriatum) would have a stronger negative phototropic response in the blue wavelength of the light in comparison to A. marginata and other color treatments. Kelp haptera were isolated and exposed to unidirectional red, green, and blue light for 16 days. Controls were exposed to unidirectional sunlight or no light. The hypothesis was mostly confirmed. The blue light exposure showed the highest phototropic response in both species, but a higher relative response in A. fimbriatum. Alaria marginata haptera responded to all wavelengths of light. Green exposure produced the lowest response in all species Moreover, it was discovered that red light was responsible for greater growth of haptera in A. marginata than other treatments colors. The mechanism and ecological implications of red light-driven hapteral growth are opportunities for further research.
Keywords: Kelp, Colors, Light, Alaria marginata, Agarum fimbriatum, deep, shallow, growth, haptera, negative phototropism